(untitled) (EU and comparative law issues and challenges series (ECLIC), 2019)
During 2017, at the level of the European Union, two regulations of importance for the suppression of criminal offenses against the EU financial interests have been passed: Directive on the fight against fraud to the Union’s financial interests by means of criminal law and Regulation implementing enhanced cooperation on the establishment of the European Public Prosecutor’s Office (EPPO). The protection of these interests by the criminal substantive legislation did not encounter such resistance in the Member States as an idea of the establishment of the EPPO. Pursuant to the provisions of Regulation implementing enhanced cooperation on the establishment of the EPPO are carried out by national delegated prosecutors, and the criminal proceedings are conducted by the courts of the Member States. The experience of the public prosecutors and judges in proceedings concerning those criminal offenses may also enhance knowledge and skills of relevance to the conduct of proceedings against perpetrators of offenses against financial interests of the Member States’. In the paper authors are trying to point out the importance of timely and adequate sanctioning the perpetrators of the above-mentioned crimes. Consequently authors point to the advantages of establishing the European Public Prosecutor’s Office in order to combat crimes that damage not only the financial interests of the European Union, but also the national financial interests. However, the concept of the European Public Prosecutor is not fully accepted, because the Regulation contains illogicalities that still make it unacceptable for member states. Therefore, in order for wider acceptance the establishment of the EPPO, it is necessary to amend these provisions of the Regulation.